DIFFERENCES IN LEXICAL INTENSITY IN ONLINE AND PRINT VERSION TITLES (Educa Journal of Studies, 2026)
This article studies the differences between the lexical intensity indicators in the headlines of online and print media based on a comparative analysis. The study is based on more than 300 headlines of major Uzbek, Russian, and English-language publications — Kun.uz, Daryo.uz, Gazeta.uz (online), "O'zbekiston Ovozi", "Xalq so'zi", "Narodnoe slovo" (print) — for the period 2020–2024. Lexical intensity is understood as the level of emotional intensity of the headline, the density of expressive means, and the potential for impact on the reader. The article analyzes such intensity means as amplification, hyperbole, oxymoron, emotional evaluative lexicon, and word repetition with examples. According to the results of the study, the lexical intensity indicator in the headlines of online publications is on average 2.3 times higher than that of print publications. The main reasons for this difference are given as format-specific communicative goals, competitive environment, reader behavior model, and editorial policy.
Keywords: Lexical intensity, headline linguistics, online media, print media, expressiveness, amplification, hyperbole, media linguistics, clickbait, lexical analysis.